The Tombs - Cussler, Clive; Perry, Thomas 1947-; Brick, Scott (New York : Penguin Audio, 2012)
Enlisted by an archaeologist friend to help excavate a top-secret historical site, husband-and-wife team Sam and Remi Fargo discover clues alluding to the hidden tomb and treasure of Attila the Hun and embark on a high-stakes chase through numerous countries.
Unabridged.
Compact discs.
Read by Scott Brick.
Keywords: Archaeologists -- Fiction; Tombs -- Fiction; Treasure troves -- Fiction; Adventure fiction; Audiobooks